Surface modification of halide perovskite using EDTA-complexed SnO2 as electron transport layer in high performance solar cells - Marques, Nuno (2024)
Publisher Copyright: © 2024 The Royal Society of Chemistry. This work is funded by FCT-MCTES (Fundação para a Ciência e Tecnologia, I. P.) via the postdoctoral grant SFRH/BPD/123502/ 2016, under the projects LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nanomodelling and Nanofabrication—i3N, and by the projects FlexSolar (PTDC/CTM-REF/1008/2020), SpaceFlex (2022.01610.PTDC) and M-ECO2 (Industrial cluster for advanced biofuel production, Ref. C644930471-00000041) co-nanced by PRR - Recovery and Resilience Plan of the European Union (Next Generation EU). This work also received funding from the European Community's H2020 program under the projects DIGISMART (grant agreement no. 787410, ERC-2018-AdG) and SYNERGY (H2020-WIDESPREAD-2020-5, CSA, proposal no. 952169). We acknowledge Jonas Deuermeier and Tomás Calmeiro for their help in XPS and AFM measurements, respectively.